Contributing Factors of Adult Adoptees' Identity Work and Self-Esteem: Family Communication Patterns and Adoption-Specific Communication. Issue 3 (2nd July 2016) - Horstman, Haley Kranstuber; Colaner, Colleen Warner; Rittenour, Christine E.
ABSTRACT: Drawing from family communication patterns (FCP) theory and the communication-based conceptual model of adoptive identity work (Colaner & Soliz, 2015), we investigated the ways that families' adoption-focused communication and general communication environment predict identity work and self-esteem in adult adoptees ( n = 143). Specifically, we tested the assumption that FCP (i.e., conversation and conformity orientation) serve as a backdrop for adoption communication openness and adoptive identity work. Structural equation modeling revealed that conversation orientation—but not conformity orientation—significantly predicted adoptive parents' communicated openness about adoption. Adoption communication openness negatively predicted adoptees' preoccupation with adoption. Indirect paths between conversation orientation, adoption communication openness, and adoptive identity and self-esteem illuminated the importance of the general communication environment on adoption outcomes. Implications are explored for expanding understanding of adoptive family communication and advancing FCP theory by testing its nature as a context-specific and/or global assessment of family communication.